Renal Trauma in the West of Ireland — A Regional Review - O. A. Raheem; M. S. Floyd; R. G. Casey; I. M. Cullen; M. O. Corcoran; H. C. Bredin; K. Walsh; C. O'Riordan; P. A. McCarthy; E. Rogers (The Scientific World Journal)
There is a paucity of data regarding renal trauma. The majority of cases of renal trauma are amenable to conservative management. We sought to streamline the management of renal trauma in the west of Ireland. Patients presenting with a computerised tomogram–confirmed renal injury were assessed over 5 years. Patient demographics, injury details, initial emergency department management, definitive management, and follow-up were assessed. Renal trauma was graded in a blind fashion (I-V). Twenty-five patients were identified; male:female (23:2). The mean age was 26 years. The majority of renal traumas were managed conservatively (92%); 8% patients underwent nephrectomy. The common mechanisms of renal injuries were road traffic accidents (44%). The majority of cases of renal injuries occur as a result of blunt trauma and can be conservatively treated. Two nephrectomies (8%) were performed. We believe this study potentially can be beneficial as part of an all-Ireland trauma database to improve patient outcome.